Inspiratory capacity is not altered in operable chronic thromboembolic pulmonary hypertension - Richter, Manuel J. (Pulm Circ, 2017)
Pathological alterations of inspiratory capacity (IC) have been observed in pulmonary hypertension. However, the clinical significance of IC in operable chronic thromboembolic pulmonary hypertension (CTEPH) without other pulmonary diseases remains unknown. CTEPH patients scheduled for pulmonary endarterectomy were prospectively screened. Despite being associated with functional capacity, pathological alterations of IC were not observed.